(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2026)
In this study, three different types of commercial solid detectors (CR-39, CN-85 and LR-115) were used for alpha particle detection, which are the most common and widely used in scientific laboratories for alpha particle detection. The detectors were cut and irradiated with a 570 kBq Americium (Am-241) radioactive source for 3 hours. After that, the detectors were immersed in NaOH solution for chemical scraping at different temperatures. An optical microscope was used to calculate the tracks of alpha particles, which are the traces and diameters of the alpha particles resulting from the irradiation, as well as the sensitivity and scraping efficiency of the detectors. Through calculations and practical results, it became clear that the LR-115 detector had the highest alpha path density (602 tr./mm²), while the CR-39 detector showed the largest path diameter (2µm), highest sensitivity (1.667), and highest efficiency (0.398) compared to the other detectors.